Comparative Transcriptome Analysis Uncovers the Regulatory Roles of MicroRNAs Involved in Petal Color Change of Pink-Flowered Strawberry - Yue, Jingyu; Liu, Zhixiang; Zhao, Can; Zhao, Jun; Zheng, Yang; Zhang, Hongwei; Tan, Changhua; Zhang, Zhentang; Xue, Li; Lei, Jiajun (Frontiers in Plant Science, 2022)
The pink-flowered strawberry is popular in China due to its high ornamental value. In the present study, sRNAome, transcriptome, and degradome sequencing were performed to understand the functions of miRNAs and their target genes during flower development in pink-flowered srawberry. Nine small RNA libraries and a mixed degradome library from flower petals at different developmental stages were constructed and sequenced. A total of 739 known miRNAs and 964 novel miRNAs were identified via small RNA sequencing, and 639 miRNAs were identified to cleave 2816 target genes based on the degradome data. Additionally, 317 differentially expressed miRNAs among the various stages of flower development were identified, which regulated 2134 differentially expressed target genes. These target genes were significantly enriched in the transcriptional regulation, phenylpropanoid biosynthesis, and plant hormone signal transduction pathways. Furthermore, integrated microRNAomic and transcriptomic analyses suggested that 98 miRNAs targeted several transcription factors, including MYBs (26), bHLHs (12), NACs (14), and SPLs (19), related to anthocyanin accumulation. In addition, 27 differentially expressed miRNAs might affect anthocyanin biosynthesis by regulating 23 targets involved in the hormone signal transduction pathway. The qRT-PCR analysis confirmed the expression changes of 21 miRNA-target pairs. Furthermore, the transient expression of candidate miRNAs was performed in the pink-flowered strawberry cultivar ‘Fenyun’ at the bud stage. Introduction of FamiR156a, FamiR396e, and FamiR858_R-2 in the ‘Fenyun’ increased flower color intensity, while transient expression of FamiR828a decreased flower color intensity. Overall, the present study uncovers the regulatory functions of microRNAs, including anthocyanin biosynthesis, hormone signaling, and regulation factors during flower development and coloration in pink-flowered strawberry. This work expands the knowledge of miRNAs affecting coloration in strawberry and provides rich resources for future functional studies.